2014
DOI: 10.3109/0142159x.2014.909585
|View full text |Cite
|
Sign up to set email alerts
|

Improving ward round skills

Abstract: RESULTS provide evidence that the presented program is a feasible and efficient tool for teaching ward round skills at the bedside. Further research should focus on cost effectiveness compared to alternative models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…On-ward supervision has already proven to be well accepted in preliminary work [17] and is also effective in improving ward round skills [53]. In the present study, video feedback was perceived to enhance teacher-directed feedback.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…On-ward supervision has already proven to be well accepted in preliminary work [17] and is also effective in improving ward round skills [53]. In the present study, video feedback was perceived to enhance teacher-directed feedback.…”
Section: Discussionmentioning
confidence: 59%
“…To determine the added value of filming patient interactions, future research should aim to objectively assess the added benefit to the supervision programme [17, 53] when integrating video-feedback, in terms of a justification study [59]. Moreover, it is unclear whether the benefits of video-based, on-ward supervision are higher for some skills or procedures than for others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study has identified deficits in final‐year medical students’ ward round competencies . Teaching ward round competencies to medical students and newly graduated doctors through simulation and observed practice has been explored, but this is time and resource intensive . A number of teams have developed ward‐round checklists, and have demonstrated their value for improving care and safety on ward rounds, but a key limitation of this is the resistance to a ‘checklist approach’ to medicine .…”
Section: Introductionmentioning
confidence: 99%
“…As the interviewed final-year medical students perceived on-ward teaching as an important resource to improve their knowledge, team integration, and enthusiasm for work, these should serve as linchpins for curricular changes. Implemented guidance, supervised on-ward teaching, 27 , 46 personal assumption of clinical responsibilities, 47 and the training of relevant clinical skills prior the start of the final year 23 , 48 have been previously shown to be essential parts in final-year medical education. However, effective team communication and conflict management trainings 36 could additionally empower students to deal with conflict.…”
Section: Discussionmentioning
confidence: 99%